2011
DOI: 10.1111/j.1369-1600.2011.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide significant association between alcohol dependence and a variant in the ADH gene cluster

Abstract: Alcohol dependence (AD) is an important contributory factor to the global burden of disease. The etiology of AD involves both environmental and genetic factors, and the disorder has a heritability of around 50%. The aim of the present study was to identify susceptibility genes for AD by performing a genome-wide association study (GWAS). The sample comprised 1,333 male in-patients with severe DSM-IV AD and 2,168 controls. These included 487 patients and 1,358 controls from a previous GWAS study by our group. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
165
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(172 citation statements)
references
References 25 publications
4
165
0
3
Order By: Relevance
“…The genetic contribution to vulnerability to develop alcohol or drug dependence has generally been estimated in the range 40-70%, depending on the substance, consistent with complex inheritance in which multiple genes exert a small effect of vulnerability or protection, A genetic meta-analysis D Li et al along with the environment (Frank et al, 2012;Gelernter and Kranzler, 2009;Goldman et al, 2005;Heath et al, 2011;Kendler et al, 2007;Wang et al, 2013). By analyzing potential associations between specific alleles and multiple substance phenotypes, our analyses may represent a necessary step toward identifying the effects of phenotypeinfluencing genes with improved certainty.…”
Section: Discussionmentioning
confidence: 73%
“…The genetic contribution to vulnerability to develop alcohol or drug dependence has generally been estimated in the range 40-70%, depending on the substance, consistent with complex inheritance in which multiple genes exert a small effect of vulnerability or protection, A genetic meta-analysis D Li et al along with the environment (Frank et al, 2012;Gelernter and Kranzler, 2009;Goldman et al, 2005;Heath et al, 2011;Kendler et al, 2007;Wang et al, 2013). By analyzing potential associations between specific alleles and multiple substance phenotypes, our analyses may represent a necessary step toward identifying the effects of phenotypeinfluencing genes with improved certainty.…”
Section: Discussionmentioning
confidence: 73%
“…7,10,11 The relevant role of genetic factors both on alcohol consumption and dependence has been clearly demonstrated by genome-wide association study (GWAS) studies. [12][13][14][15][16] Moreover, studies on the genetic variations in bitter taste receptors have also shown that variations in TAS2R16 and TAS2R38 genes can influence alcohol intake [17][18][19] but not dependence. 19 On the contrary, very little is known about the possible contribution of genetic factors to alcohol preferences in humans.…”
Section: Introductionmentioning
confidence: 99%
“…flush, nausea, and sweating) which reduces the likelihood of continued EtOH consumption (Peng and Yin, 2009). Recent research has established a polygenic contribution of the ADH gene cluster outlining a likely role for several ADH genes in the development of alcoholism (Frank et al, 2011). Alterations in the ALDH2 gene, and the subsequent increase in ACD following EtOH consumption, have been thoroughly documented as protective in nature, with regard to the development of alcoholism amongst Asian populations (Ball, 2008).…”
Section: Introductionmentioning
confidence: 99%